PENINGKATKAN MOTIVASI DAN KEMAMPUAN BERPIKIR TINGKAT TINGGI SISWA MELALUI PEMBELAJARAN PREDICT-OBSERVE-EXPLAIN PADA MATERI KERAGAMAN HAYATI - Arbayati Arbayati (Biopedagogia, 2020)
Motivation to learn is the power to direct or maintain a goal in learning. Learning motivation is able to influence students' thinking ability. Students' learning motivation and thinking skills can be improved through active learning, namely predict-observe-explain (POE). This study aims to increase students' motivation and higher order thinking skills through the implementation of POE in biodiversity learning. This classroom action research consisted of two cycles, with a sample of 37 students. This research was conducted in August-September 2020 which consisted of planning, implementing actions, observing, and reflecting. The research instrument consisted of a learning motivation questionnaire and a test of biodiversity description. The results showed that the mean learning motivation in the first cycle was 58.37 in the criteria of sufficiently motivated, in the second cycle 64.97 was categorized as sufficiently motivated and the average high level thinking ability of students in the first cycle was 53.51, then there was an increase in the second cycle, namely 79.27. The conclusion in this study is the application of the POE model can improve learning motivation and high-order thinking skills of class X MIPA 2 SMA Negeri 3 Tarakan on the subject of Biodiversity. Keywords:  Motivation, higher order thinking skill, predict observe explain